First-principles Measurement of Ion and Electron Energization in Collisionless Accretion Flows - Evgeny A. Gorbunov; Fabio Bacchini; Vladimir Zhdankin; Gregory R. Werner; Mitchell C. Begelman; Dmitri A. Uzdensky (The Astrophysical Journal Letters)
We present the largest 3D particle-in-cell shearing-box simulations of turbulence driven by the magnetorotational instability, for the first time employing the realistic proton-to-electron mass ratio. We investigate the energy partition between relativistically hot electrons and subrelativistic ions in turbulent accreting plasma, a regime relevant to collisionless, radiatively inefficient accretion flows around supermassive black holes such as those targeted by the Event Horizon Telescope. We provide a simple empirical formula to describe the measured heating ratio between ions and electrons, which can be used for more accurate global modeling of accretion flows with standard fluid approaches such as general-relativistic magnetohydrodynamics.